A highly creative endeavour: Interview with musicologist and silent film pianist Martin Marks. Issue 1 (1st November 2020) - Tieber, Claus; Windisch, Anna K.
Martin Marks holds an almost unique position to talk about silent film music: he is a scholarly musician and musical scholar. Besides his canonical book on the history of silent film music (1997), he has been playing piano accompaniments for silent films regularly for nearly four decades. In this interview we asked Martin about the challenges and complexities of choosing and creating music to accompany musical numbers in silent cinema. Martin relates how he detects musical numbers and he expounds his decision-making process on how to treat them. His explanations are interspersed with engaging examples from his practical work and based on both his scholarly knowledge and on his musical intelligence. He talks about the use of pre-existing music as well as about anachronisms in choosing music written many decades after a film was first released. In sum, this interview delivers detailed and informed insights into the difficulties and pleasures of accompanying musical numbers or other types of diegetic music in silent cinema.